INTERNATIONAL EXPERIENCES IN COOPERATIVE AUDIT AND LESSONS FOR SERBIA - Vladimir Zakić; Marija Nikolić; Vlado Kovačević (Ekonomika Poljoprivrede (1979), 2018)
Basic characteristics of cooperative audit, its role in preservation of cooperative nature and promotion of cooperatives are analyzed in the paper. The aim of this paper is to propose measures to improve cooperative audit in Serbia based on the review of good practice in European countries.